Youth and ICTs: An attractive opportunity - Tia, Moses N. (Technical Centre for Agricultural and Rural Cooperation, 2012)
Audio conferencing has helped to improve extension services in northern Ghana, and encouraged young people in rural communities to follow a career in agriculture